How Applied English Students’ Dealing with Literary Translation - Fitri Alfarisy (Anuva: Jurnal Kajian Budaya, Perpustakaan, dan Informasi, 2020)
The graduate students of Applied English are expected to have skills on translations needed by the industry. They are expected to be able to translate any kinds of texts either formal, advertisement, directions or literary. The translation of the literature differs from other forms of translation. It is interesting to find out the ways the applied students dealing with literary translations. In collecting the data, document analysis in the form of analyzing the students work and interviews were done. The result showed that translation literary works is not an easy job for applied English students when they do not have the theory related and not familiar with. Based on the study, it was found that several mistakes are committing by the students when translating the literary works such as using literal translation, misunderstanding the context, having over confidence and lacking vocabularies. On the other hand, the students realized their mistakes well and understand that through reading a lot, improving the vocabularies and having more experiences will ease them to deal with the literary translation.